'That fantasy that you can deal with everything yourself and move mountains', an examination of men's beliefs and media representations about mental health services : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Gallagher, Jake Marek (Massey University, 2021)
Young men tend to be less likely to seek help for mental distress due to barriers to help-seeking. Lack of knowledge and negative attitudes regarding services is one such barrier to help-seeking; however, little research examines what men who have not accessed services believe services involve. Likewise, there is little research assessing how services are presented in news media. This project comprised two studies designed to address these gaps in the literature. Both studies utilised inductive thematic analysis within a social constructionist epistemology to examine possible influences on men’s help-seeking. Study One aimed to develop an understanding of young men’s beliefs about mental health treatment when they have not utilised such services. Ten young men who had not accessed services participated in a semi-structured one-on-one interview. Participants expressed a preference to fix problems independently if possible, negative views of the possibility of relying on prescription medication, and they likened talk-therapy to informal social supports. They also acknowledged the limits of their understanding of services, stating that most of their beliefs were based on fictional depictions of services, and that in a consultation they would likely listen to their doctor’s advice. It was concluded that better public education regarding services and treatment may affect attitudes and behaviours towards services; however, the culturally embedded imperative to deal with problems independently also requires challenging. Study Two aimed to understand how services were presented in digital news media. A preliminary quantitative content analysis identified recent rates of mental health reporting on the news platforms Stuff and NZ Herald. Articles were taken from May and February 2019, the most recent peak and trough, respectively, of mental health related articles. Thematic analysis of these articles indicated that news media presented positive outcomes of mental illness through recovery. However, articles also stated that services were underfunded, and understaffed, that mental illness is a rising issue in New Zealand, and that government was not doing enough to improve services. Thus, although the news media gave the message that recovery is possible, it also framed services as struggling, which may have implications for intentions to help-seek.
Keywords: Mental health services; New Zealand; Young men; Attitudes; Mental health services; Press coverage; 520304 Health psychology